The Effect of Firm Size, Profitability, and Leverage on Tax Aggressiveness: Evidence from Consumer Non-Cyclicals Companies Listed on the Indonesia Stock Exchange (2020–2024) - Achmad Kurniawan Syabana; Maya Safira Dewi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Tax revenue constitutes the primary source of government income in Indonesia and plays a crucial role in financing national development. Nevertheless, tax aggressiveness remains one of the major challenges faced by tax authorities because it reduces government revenue and weakens fiscal sustainability. Tax aggressiveness refers to corporate strategies designed to minimize tax liabilities through various tax planning practices, ranging from legal tax avoidance to more aggressive approaches that exploit regulatory loopholes. The Consumer Non-Cyclicals sector represents one of the most resilient industries in Indonesia due to its stable demand and relatively consistent financial performance. These characteristics provide companies with opportunities to optimize financial policies, including tax management strategies. Consequently, understanding the determinants of tax aggressiveness has become increasingly important for both policymakers and corporate stakeholders. This study aims to examine the effect of firm size, profitability, and leverage on tax aggressiveness among Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Specifically, the study investigates the individual and simultaneous effects of these financial characteristics on corporate tax aggressiveness. The study adopts a quantitative approach using descriptive and verificative research designs. Secondary data were collected from annual reports of publicly listed companies. The research population consisted of 132 Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange. Using purposive sampling, 80 companies were selected as research samples, resulting in 400 firm-year observations. Data were analyzed using panel data regression, preceded by descriptive statistical analysis, model selection, classical assumption testing, hypothesis testing, and coefficient of determination analysis. The findings indicate that firm size, profitability, and leverage significantly influence tax aggressiveness, both individually and simultaneously. These results suggest that corporate financial characteristics play an important role in shaping management decisions related to tax planning strategies. Larger firms possess greater organizational resources to manage tax obligations, while profitability and leverage influence managerial incentives and financing structures that affect tax behavior. This study contributes to the literature on taxation and corporate finance by providing recent empirical evidence from Indonesia’s Consumer Non-Cyclicals sector during the post-pandemic economic recovery period. The findings are expected to assist corporate managers in developing prudent tax planning strategies and provide useful insights for tax authorities in identifying corporate characteristics associated with tax aggressiveness.